Body mass index and clinical outcome of severe COVID-19 patients with acute hypoxic respiratory failure: Unravelling the "obesity paradox" phenomenon. (October 2022) - Jennings, Michael; Burova, Maria; Hamilton, Laura G.; Hunter, Elsie; Morden, Clare; Pandya, Darshni; Beecham, Ryan; Moyses, Helen; Saeed, Kordo; Afolabi, Paul R.; Calder, Philip C.; Dushianthan, Ahilanandan; et al.
Summary: Background and aims: Although obesity have been generally shown to be an independent risk factor for poor outcomes in COVID-19 infection, some studies demonstrate a paradoxical protective effect ("obesity paradox"). This study examines the influence of obesity categories on clinical outcomes of severe COVID-19 patients admitted to an intensive care unit with acute hypoxic respiratory failure requiring either non-invasive or invasive mechanical ventilation. Methods: This is a single centre, retrospective study of consecutive COVID-19 patients admitted to the intensive care unit between 03/2020 to 03/2021. Patients were grouped according to the NICE Body Mass Index (BMI) category. Admission variables including age, sex, comorbidities, and ICU severity indices (APACHE-II, SOFA and PaO2/FiO2) were collected. Data were compared between BMI groups for outcomes such as need for invasive mechanical ventilation (IMV), renal replacement therapy (RRT) and 28-day and overall hospital mortality. Results: 340 patients were identified and of those 333 patients had their BMI documented. Just over half of patients (53%) had obesity. Those with extreme obesity (obesity groups II and III) were younger with fewer comorbidities, but were more hypoxaemic at presentation, than the healthy BMI group. Although non-significant, obesity groups II and III paradoxically showed a lower in-hospital mortality than the healthy weight group. However, adjusted (age, sex, APACHE-II and CCI) competing risk regression analysis showed three-times higher mortality in obese category I (sub-distribution hazard ratio = 3.32 (95% CI 1.30–8.46), p = 0.01) and a trend to higher mortality across all obesity groups compared to the healthy weight group. Conclusions: In this cohort, those with obesity were at higher risk of mortality after adjustment for confounders. We did not identify an "obesity paradox" in this cohort. The obesity paradox may be explained by confounding factors such as younger age, fewer comorbidities, and less severe organ failures. The impact of obesity on indicators of morbidity including likelihood of requirement for organ support measures was not conclusively demonstrated and requires further scrutiny.